2017
DOI: 10.1159/000477873
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Insulin-Like Growth Factor Binding Protein-4 Overexpression Inhibits Osteogenic Differentiation of Rat Mesenchymal Stem Cells

Abstract: Background/Aims: Insulin-like growth factor binding proteins (IGFBP) play important roles in bone metabolism. IGFBP4 is involved in senescent-associated phenomena in mesenchymal stem cells (MSCs). The goal of the present study was to determine whether age-related IGFBP4 overexpression is associated with the impaired osteogenic differentiation potential of aged bone marrow derived MSCs. Methods: MSCs were isolated from Sprague-Dawley rats aged 3-26 months. The bone morphogenetic protein (BMP)-2-induced osteogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Silencing mitofusin-2 has been found to inhibit MSC senescence induced by the abrogation of FGF21 as well. Knockdown of insulin-like growth factor binding protein 4 restored the osteogenic potency of aged MSCs via the activation of Erk and Smad signals[ 110 ]. Pretreatment of aged MSCs with macrophage migration inhibitory factor (MIF) enhanced the secretion of vascular endothelial growth factor (VEGF), bFGF, hepatocyte growth factor, and insulin-like growth factor, which promoted their growth, paracrine function, and survival[ 80 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…Silencing mitofusin-2 has been found to inhibit MSC senescence induced by the abrogation of FGF21 as well. Knockdown of insulin-like growth factor binding protein 4 restored the osteogenic potency of aged MSCs via the activation of Erk and Smad signals[ 110 ]. Pretreatment of aged MSCs with macrophage migration inhibitory factor (MIF) enhanced the secretion of vascular endothelial growth factor (VEGF), bFGF, hepatocyte growth factor, and insulin-like growth factor, which promoted their growth, paracrine function, and survival[ 80 ].…”
Section: Cellular Rejuvenation Strategiesmentioning
confidence: 99%
“…IGFBP4 can act as an inhibitor of the canonical Wnt signaling required for cardiogenesis and provides a molecular link between IGF signaling and Wnt signaling [31]. There is evidence that IGFBP4 expression increases with age and is associated with the impairment of MSC differentiation via the Erk and Smad pathway [32]. Consistent with previous studies that indicated IGFBP4 as a key component needed for triggering senescence in young MSC and a harmful factor that impair the habituation learning, which is correlated with cognitive function [20, 33], our present study demonstrated that IGFBP4 was up-regulated in the plasma of aged compared with young subjects and that injection of IGFBP4 into mice also accelerates cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted by β cells of the pancreas, insulin is a potent anabolic hormone in stem cell differentiation and bone formation (Wu et al 2017). Interestingly, at the early stage of osteogenic differentiation of MC-3T3 cells (days 3 to 6), IGF-I and IGFBP-2 activated the AMPK pathway and enhanced the phosphorylation of ULK-1 S555 (a known AMPK phosphorylation site in ULK-1 that is necessary to assemble the essential components of autophagosome) and the expression of beclin-1 and LC3-II, which indicated the stimulation of autophagy.…”
Section: Discussionmentioning
confidence: 99%